Detection of Age-Related Macular Degeneration by Portable Optical Coherence Tomography Operated by Nonexpert Personnel: Potential Use for Screenings. (January 2019) - Cho, Chris; Liu, Melissa M.; Channa, Roomasa; Zhang, Alice Y.; Quigley, Harry A.; Jefferys, Joan L.; Scott, Adrienne W.
Purpose: The purpose of this study is to determine the sensitivity and specificity of detecting age-related macular degeneration (AMD) using portable optical coherence tomography (OCT) operated by nonexpert photographers on undilated patients. Methods: In this case-control study, 92 individuals were recruited from the glaucoma and retina clinics at the Wilmer Eye Institute (Johns Hopkins University, Baltimore, MD). Using the portable iVue (Optovue, Inc, Fremont, CA) spectral-domain OCT (SD-OCT), 2 nonexpert photographers acquired retina map scans on undilated eyes of all participants. In total, 33 AMD eyes and 105 control eyes were evaluated and graded by ophthalmologists masked to the diagnoses. Results: Detection of AMD on the portable OCT by ophthalmologists exhibited sensitivities of 0.91 and 0.94 and specificities of 0.88 and 0.89, for graders 1 and 2, respectively. A strong intergrader agreement was observed (κ = 0.87). Conclusions: Nonexpert photographers can use a portable OCT on undilated eyes to acquire images for the detection of AMD. These findings present the potential utility of implementing a portable OCT in community screenings for earlier detection and treatment of disease.